Estratégia de aquisição lexical: relações com o livro didático de língua portuguesa - Mulinari, Eudes Terezinha Nadal (2014)
This research investigated the activities proposed for the lexicon development in two collections of textbooks for the Portuguese teaching in the final years of Elementary School Books, understanding that lexical acquisition is a complex process and a factor of great importance in reading comprehension. The collections Português Linguagens e Projeto Teláris - first and second place, relatively, in the educational book distribution in the country according to the 2014 PNLD were analyzed. Investigations in the area of vocabulary teaching have shown that lexical acquisition can be strategic, which promotes a continuous and autonomous development of this competence (FINGER-KRATOCHVIL, 2010; CAIN, 2009; LEFFA, 1996). With theoretical support in Psycholinguistics studies, we confirm, in the vocabulary of those collections activities, the presence of instructions for the use of the three main strategies for lexicon acquisition: the use of context, morphological clues and the dictionary (GRAVES, 2006). We also observed the frequency of these activities and how they are presented. The strategic use of that knowledge is related to metacognitive behavior, in other words, when the student / reader uses resources to deliberate control of the process of understanding itself. However, being strategic is something that is learned, and therefore, it is necessary a proposal for the teaching and learning of vocabulary with a view to the formation of strategic and critical readers. In this research, we present an analysis of qualitative and quantitative data contents of both collections. Results indicated that teaching strategies is keen, because it was not possible to observe explicit instructions for the use of lexical acquisition strategies; how to develop them and to use them. Among the activities that had potential for strategic work, the ones which use contextual clues are the most frequent, followed by the use of the dictionary and morphological clues. These considerations point to the fact that teaching vocabulary, whether incidental or intentional, with development of metacognitive awareness, still requires theoretical and methodological investment in this, which is the most available resource for teachers in Brazil nowadays, the textbook.